Performance Evaluation of Carbon Fiber Reinforced with Polyethylene Terephthalate Glycol (PETG) in Additive Manufacturing - Nerella Mary Jasmin; Kumar Rajesh; L. Girisha; Vinoth R.; Ram S.; Thakur Gaurav; Verma Anjali (E3S Web of Conferences)
This research worked on the mechanical properties of Carbon Fiber Reinforced Polyethylene Terephthalate Glycol (PETG) for applications in 3D printing. Carbon fiber reinforcement was incorporated into PETG and pellets as the base material. Tensile and compression tests were conducted on Carbon fiber-reinforced PETG and PETG to appraise the respective mechanical strength and stiffness. The results of these test coupled with comparisons between the two materials, provided valuable insights into the performances and potential application of Carbon fiber-reinforced PETG in additive manufacturing. The research contributed to understanding Carbon Fiber Reinforced PETG’s mechanical behavior, decisive for engineering applications. The highest tensile strength recorded for Carbon Fiber PETG was 38.51 MPa, achieved in sample 7 by infill density of 100%, a layer height of 0.30mm, and a printing speed of 40mm/s. The highest compression strength recorded for normal PETG was 52.29 MPa, observed in sample 8. under different parameters infill density of 100%, a layer height of 0.18mm, and a printing speed of 60mm/s.